Performance analysis and optimal design of MU-MIMO transmission scheme based on IEEE 802.11ac - Bao-feng JI; Kang SONG; Yong-ming HUANG; Lv-xi YANG (Tongxin xuebao, 2013)
The recent IEEE 802.11ac adopted a novel multi-user access technique,which was the downlink multi-user MIMO (MU-MIMO) transmission.This was very different from the former IEEE 802.11 standard's protocols.The MU-MIMO transmission technique in IEEE 802.11ac draft was studied and proposed some optimal designs.Finally,the performance of the IEEE 802.11ac MU-MIMO transmission schemes and gives the simulations.The simulation results show that the proposal transmission schemes can achieve gains of BER and throughput in theory and simulations.